2012
DOI: 10.1002/bdm.1757
|View full text |Cite
|
Sign up to set email alerts
|

Strategy Selection in Risky Choice: The Impact of Numeracy, Affect, and Cross‐Cultural Differences

Abstract: Real-world decisions often involve options with outcomes that are uncertain and trigger strong affect (e.g., side effects of a drug). Previous work suggests that when choosing among affect-rich risky prospects, people are rather insensitive to probability information, potentially compromising decision quality. We modeled the strategies of less and more numerate participants in the United States and in Germany when choosing between affect-rich prospects and between monetarily equivalent affect-poor prospects. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
82
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 34 publications
9
82
0
2
Order By: Relevance
“…It is measured with questions like those in the standard 11-item numeracy scale of Lipkus, Samsa, and Rimer (2001), such as BThe chance of getting a viral infection is .0005. Out of 10,000 people, about how many of them are expected to get infected?^In choice tasks, more numerate individuals are less influenced by positive versus negative problem frames, frequency versus probability risk format (Pachur & Galesic, 2013;Peters, Västfjäll, Slovic, Mertz, Mazzocco, & Dickert, 2006), and narrative information (Dieckmann, Slovic, & Peters, 2009). More numerate individuals also tend to have less difficulty with utility elicitation (see Reyna, Nelson, Han, & Dieckmann, 2009, for a review), and are more likely to adopt number-based decision strategies than to rely on other decision heuristics, such as intuition (Cokely & Kelley, 2009;Pachur & Galesic, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is measured with questions like those in the standard 11-item numeracy scale of Lipkus, Samsa, and Rimer (2001), such as BThe chance of getting a viral infection is .0005. Out of 10,000 people, about how many of them are expected to get infected?^In choice tasks, more numerate individuals are less influenced by positive versus negative problem frames, frequency versus probability risk format (Pachur & Galesic, 2013;Peters, Västfjäll, Slovic, Mertz, Mazzocco, & Dickert, 2006), and narrative information (Dieckmann, Slovic, & Peters, 2009). More numerate individuals also tend to have less difficulty with utility elicitation (see Reyna, Nelson, Han, & Dieckmann, 2009, for a review), and are more likely to adopt number-based decision strategies than to rely on other decision heuristics, such as intuition (Cokely & Kelley, 2009;Pachur & Galesic, 2013).…”
mentioning
confidence: 99%
“…Out of 10,000 people, about how many of them are expected to get infected?^In choice tasks, more numerate individuals are less influenced by positive versus negative problem frames, frequency versus probability risk format (Pachur & Galesic, 2013;Peters, Västfjäll, Slovic, Mertz, Mazzocco, & Dickert, 2006), and narrative information (Dieckmann, Slovic, & Peters, 2009). More numerate individuals also tend to have less difficulty with utility elicitation (see Reyna, Nelson, Han, & Dieckmann, 2009, for a review), and are more likely to adopt number-based decision strategies than to rely on other decision heuristics, such as intuition (Cokely & Kelley, 2009;Pachur & Galesic, 2013). They also show greater probability sensitivity (Reyna et al, 2009) in that they modulate their choice behavior in response to even small changes in given probabilities, and they have better-calibrated subjective probability judgments (Winman, Juslin, Lindskog, Nilsson, & Kerimi, 2014); that is, judgments that more closely match actual relative frequencies.…”
mentioning
confidence: 99%
“…Crucially, people high in numeracy more frequently and efficiently incorporate probability information in the decision-making process (Peters et al, 2006), which results in more rational choices (Pachur & Galesic, 2013) probably through drawing more precise affective meaning from numbers (Petrova et al, 2014). To date, little is known about the exact link between attentional engagement to numerical information and numeracy.…”
Section: Discussionmentioning
confidence: 99%
“…A similar effect (i.e., a larger insensitivity to changes in numerical features of risky prospects) emerges when the magnitude of a stimulus (e.g., monetary value) is evaluated by feelings rather than by calculation (Hsee & Rottenstreich, 2004). In the same vein, it has recently been shown that people pay less attention to probability information in affectrich than affect-poor decision problems what results in suboptimal choices (Pachur & Galesic, 2013). Importantly, in cases of affect-poor decision problems, people base their choices on compensatory strategies -they use weighting and summing processes to make the trade-off between payoffs and probabilities within each alternative (Pachur, Hertwig, & Wolkewitz, 2014).…”
Section: Introductionmentioning
confidence: 89%
“…Experimental research provides evidence that numeracy influences strategies used for decision making and the quality of the decisions taken. Individuals with higher numeracy have superior judgment abilities (Ghazal et al 2014) and are more likely to choose the normatively better option with a higher expected value (Pachur and Galesic, 2013).…”
Section: Introductionmentioning
confidence: 99%